2013
DOI: 10.5493/wjem.v3.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of immune response in experimental Chagas disease

Abstract: Trypanosoma cruzi (T. cruzi ), the etiological agent of Chagas disease, affects nearly 18 million people in Latin America and 90 million are at risk of infection. The parasite presents two stages of medical importance in the host, the amastigote, intracellular replicating form, and the extracellular trypomastigote, the infective form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 61 publications
1
44
0
4
Order By: Relevance
“…A balance between proinflammatory and regulatory cytokines is necessary in order to control the infection [41]. Hence, the expression of proinflammatory and regulatory cytokines was evaluated by real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…A balance between proinflammatory and regulatory cytokines is necessary in order to control the infection [41]. Hence, the expression of proinflammatory and regulatory cytokines was evaluated by real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that cytokines secreted by T cells play a central role in host immune responses to T. cruzi infection by regulating the ability of infected macrophages to kill parasites (Silva et al, 2005;de Meis et al, 2008). Therefore, resistance to T. cruzi infection depends on a balance between type 1 and type 2 cytokine responses (Gazzinelli et al, 1992;Basso et al, 2004;Silva et al, 2005;Basso, 2013), but it is generally accepted that knowledge of this immunoregulation and many aspects of the pathogenesis and progression of Chagas disease remains incomplete. Moreover, current treatments for this disease are partly effective only in the acute period and are toxic.…”
Section: Introductionmentioning
confidence: 98%
“…As células Th1 são responsáveis pela produção de citocinas próinflamatórias, enquanto as células Th2 estão envolvidas na resposta controlada por anticorpos (CARDILLO et al, 2007). Então, um equilíbrio imunológico se faz necessário entre as respostas imunes mediadas por estas células, promovendo um mecanismo protetor ao hospedeiro (BASSO, 2013).…”
Section: Introductionunclassified
“…O mecanismo desta resposta imune contra o parasita se mostra complexo, envolvendo uma variedade de populações celulares. Geralmente, a imunidade inata mediada por macrófagos e células dendríticas, são responsáveis pelo reconhecimento e destruição do parasita, apresentação de antígenos e produção de citocinas inflamatórias(TARLETON, 2007;BASSO, 2013). Contudo, o controle da infecção depende da interação entre as respostas imunes, inata e adaptativa, com a participação de macrófagos, células dendríticas, células natural…”
unclassified
See 1 more Smart Citation